Fluid effect on hydraulic fracture propagation behavior: a comparison between water and supercritical CO2‐like fluid. Issue 2 (12th September 2013) - Zhou, X.; Burbey, T. J.
Abstract The initiation of hydraulic fractures during fluid injection in deep formations can be either engineered or induced unintentionally. Upon injection of CO2, the pore fluids in deep formations can be changed from oil/saline water to CO2 or CO2 dominated. The type of fluid is important not only because the fluid must fracture the rock, but also because rocks saturated with different pore fluids behave differently. We investigated the influence of fluid properties on fracture propagation behavior by using the cohesive zone model in conjunction with a poroelasticity model. Simulation results indicate that the pore pressure fields are very different for different pore fluids even when the initial field conditions and injection schemes (rate and time) are kept the same. Low viscosity fluids with properties of supercritical CO2 will create relatively thin and much shorter fractures in comparison with fluids exhibiting properties of water under similar injection schemes. Two significant times are recognized during fracture propagation: the time at which a crack ceases opening and the later time point at which a crack ceases propagating. These times are very different for different fluids. Both fluid compressibility and viscosity influence fracture propagation, with viscosity being the more important property. Viscosity can greatly affect hydraulic conductivity and the leak‐off coefficient. This analysis assumes the in‐situ pore fluid and injected fluid are the same and the pore space is 100% saturated by that fluid at the beginning of the simulation.